KAJIAN MASTERPLAN DRAINASE PASANG SURUT KOTA BANJARMASIN - Novitasari, Novitasari (Universitas Lambung Mangkurat, 2008)
The growth ofBanjarmasinCitycause increase of water burden which must be dried and land used increase caused by city growth, it’s caused that incoming rainfall concentration into surface runoff and groundwater decrease. Garbage which change the water quality in river cause the river unable to again run its role as natural drainage system. The aim of this research is give an instruction of Matrix Program of Drainage System of Banjarmasin city by root causes program. It’s consisted of identify the problem, analysis, solution and planning program.Evaluate of drainage system of BanjarmasinCity, by comparing and analysis result of technical calculation with the condition existing, obtained result that channel of exiting drainage still be adequate. So drainage system in BanjarmasinCitydoesn’t have to see as diffraction (macro) and general, but have to handing as micro solution. Existing channel need the handling O&M, also require public participate in lowest-level of drainage system management. And also need the existence of integrated system from all stakeholder that is involved in drainage system management.